2017
DOI: 10.11604/pamj.2017.27.73.12167
|View full text |Cite
|
Sign up to set email alerts
|

Functioning and disability in recent research from Cameroon: a narrative synthesis

Abstract: IntroductionPeople living with disabilities in Cameroon face many barriers to daily functioning and social participation. However, there is limited research on disabilities and their impact. We sought to examine the research related to disability from Cameroon.MethodsWe conducted a systematic review, bibliometric analysis, and narrative synthesis of research related to disability, functioning, and social participation from Cameroon published during 2005-2014. The articles were screened in duplicate to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…We have completed and published one narrative synthesis of the research conducted in Cameroon on functioning and disability. In this paper, we highlight the paucity of research on disability and the associated stigma, limited knowledge and awareness, poor quality of care and hindered employment opportunities for people with disabilities [ 10 ]. We plan to explore other fields of research including mental health and HIV.…”
Section: Opportunitiesmentioning
confidence: 99%
“…We have completed and published one narrative synthesis of the research conducted in Cameroon on functioning and disability. In this paper, we highlight the paucity of research on disability and the associated stigma, limited knowledge and awareness, poor quality of care and hindered employment opportunities for people with disabilities [ 10 ]. We plan to explore other fields of research including mental health and HIV.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Limited data on disability in Cameroon are available. However, a recent review by Ray et al (2017) identified five studies that addressed access to work amongst persons with specific impairments (for example visual impairments or related to HIV) in Cameroon, all of which documented unequal employment opportunities related to a combination of stigma, participation restrictions and restricted access to education[ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The creation of materials specifi c to the NWR and rehabilitation is particularly noteworthy as there are no sustained rehabilitation research groups based in the region, and very few resources about rehabilitation that have been developed and published specifi cally for this context (Ray, Wallace, Mbuagbaw, and Cockburn, 2017). Although still limited, the production of materials by and for practitioners was inspiring, and encouraged many members to consider how they could continue to develop professional learning materials.…”
Section: Discussionmentioning
confidence: 99%